Interobserver Variability and Distribution of Mammographic Breast Density in Patients with Invasive Breast Carcinoma using the Fifth Edition of BI-RADS Guidelines - Ab Rahman, Siti Soraya; Mohd Kamal, Luqman Hakim; Ab Rahman, Farah Hani; Ghazali, Rosliza; Saidil, Emelianah; Nor, Nadeeya Mohamad (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Breast density is associated with an increased risk of developing breast cancer. The present study aims to determine the distribution and interobserver variability of mammographic breast density in patients with invasive breast carcinoma, using the fifth edition of BI-RADS guidelines. It is part of a larger study to ascertain the association between mammographic breast density and breast cancer characteristics. MATERIALS AND METHODS: Two radiologists independently assessed 122 mammograms of patients with histologically confirmed invasive breast carcinoma and assigned the breast density to categories A-D based on the fifth edition of BI-RADS guidelines. The interobserver variability was calculated using the weighted kappa coefficient and the level of agreement was determined using the Landis and Koch guidelines. RESULTS: In this study, 55.7% of patients with invasive breast carcinoma were assigned to category B, followed by category C with 36.1%. Only 4.1% of patients were assigned to categories A and D respectively. There was substantial agreement between the two readers’ judgement, k=0.610 (95% CI, 0.523-0.697), p < 0.001 for specific BI-RADS categories. CONCLUSION: Among patients with invasive breast carcinoma, there were more patients with non-dense breasts than dense breasts. Overall, there is a substantial interobserver agreement when radiologists used the fifth edition of the BI-RADS guideline, which is in line with results found in the literature. This suggests that the BI-RADS density classification is an acceptable method and can be reliably used in clinical practice.